2019
DOI: 10.21276/ijcmr.2019.6.12.40
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Transfusion Transmitted Infections in Multiple Blood Transfused β-Thalassemia Patients from a Tertiary Care Centre in North India

Abstract: Introduction: The mainstay of therapy for patients suffering from beta thalassemia major is regular blood transfusion and chelation therapy due to constraints in bone marrow transplantation. The present study was conducted to estimate the prevalence of transfusion-transmitted infections (TTIs) in multitransfused patients of thalassemia major and to determine the association with relation to the number of blood transfusions received. Material and Methods: This study was conducted in Department of Microbiology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Our study showed highest occurrence of HCV infection 4/102 (3.90%). The highest prevalence of HCV was also seen in studies like Gugnani et al 14 of 13.4%, Sidhu et al 15 of 13.04%, Manisha et al 16 of 18.2%. Post-transfusion transmission of HCV has still remained a major health concern in multi-transfused patients.…”
Section: Discussionmentioning
confidence: 66%
“…Our study showed highest occurrence of HCV infection 4/102 (3.90%). The highest prevalence of HCV was also seen in studies like Gugnani et al 14 of 13.4%, Sidhu et al 15 of 13.04%, Manisha et al 16 of 18.2%. Post-transfusion transmission of HCV has still remained a major health concern in multi-transfused patients.…”
Section: Discussionmentioning
confidence: 66%
“…When compared to statistics available through peer-reviewed studies from India,[ 15 16 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 ] incidence of HIV-1, HBV and HCV in our thalassemia cohort was on the higher side [ Table 7 ]. Most recent reports from our country document the high prevalence of these TTIs due to the use of molecular tests in addition to serological tests like in our study [ Table 7 ].…”
Section: Discussionmentioning
confidence: 99%